2011
DOI: 10.1038/labinvest.2011.11
|View full text |Cite
|
Sign up to set email alerts
|

An orally available small imidazolium salt ameliorates inflammation and fibrosis in a murine model of cholestasis

Abstract: Hepatic fibrosis is the result of chronic liver injuries underlined by diverse etiologies. The massive accumulation of extracellular matrix (ECM) proteins during fibrogenesis leads to structural distortion and functional disruption of the liver. There is currently no effective standard treatment for liver fibrosis. We previously identified a class of imidazolium salts (IMSs) with anti-fibrotic properties in a cell-based screen. In this report, we investigated the anti-fibrotic efficacy and mechanisms of a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…It was suggested before, that changes related to ECM remodelling could lead to perturbations in intracellular signalling affecting Fxr related pathways and thereby leading to liver injuries [41]. …”
Section: Discussionmentioning
confidence: 99%
“…It was suggested before, that changes related to ECM remodelling could lead to perturbations in intracellular signalling affecting Fxr related pathways and thereby leading to liver injuries [41]. …”
Section: Discussionmentioning
confidence: 99%
“…We did not detect changes of TIMP‐1 (Fig. a), which was downregulated by DPIM treatment in the BDL model . Overall, the enhanced MMPs activities by DPIM treatment could potentially help to restore the imbalanced ECM turnover in the TAA model.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, different mechanistically distinct hepatic fibrosis animal models are required to demonstrate the efficacy of anti‐fibrotic drug candidate to exclude model‐specific effects . In a previous report, we demonstrated DPIM treatment ameliorated fibrosis in a BDL induced fibrosis model, this prompted us to further investigate the anti‐fibrotic property of DPIM in other hepatic fibrosis animal models. Here we showed that DPIM could attenuate hepatic fibrosis in a TAA‐induced hepatic fibrosis model, which is considered to be more clinically relevant .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations